SORPTION-DESORPTION CHARACTERISTICS OF HEAVY METALS AND THEIR AVAILABILITY FROM THE SEDIMENT OF SEGARA ANAKAN ESTUARY - Sri Noegrohati (Universitas Gadjah Mada, 2005)
Estuarine sediments are increasingly recognized as both a carrier and a possible source of heavy metals in pollution of aquatic ecosystems. The bioavailability of heavy metal from sediments, however, is a long-standing impediment of questions in determining the metal effects in ecosystems. The fraction considered as available heavy metal are both the dissolved heavy metal and the exchangable cations. The main objective of this study is to understand the extent of heavy metal availability from sediments in estuarine ecosystem. It was found that the availability of heavy metals, i.e. copper, zinc, cadmium, and mercury in the estuarine ecosystem investigated, are governed by the relative strength of the electrostatic attraction of their complexation to the ligands present both in the sediment and the overlaying waters. Under simulated estuarine ecosystem, it was observed that Cu and Zn prefer to form organo-complex through ligand exchange, while Cd and Hg tend to form chloro-complex through electrostatic interaction. Therefore, the availability of Hg and Cd is higher in more saline overlaying water. On the contrary, the availability of Cu and Zn is lower in more saline overlaying waters, as indicated by their respective water-sediment distribution coefficient, KD. Similar behaviour of heavy metal was observed in natural field conditions of Segara Anakan estuary. Due to the higher salinity of the overlaying water, the availability of Cd and Hg in dry season was higher than in wet season, while Zn was more available in wet season due to the higher input of organic matters from the inland. The patterns of heavy metal release from the sediment are consistent to that obtained in experiments of the undisturbed simulation, where highest release was obtained for Cd. Surprisingly, it was found that even though Cd was not detected in the sediment, higher level of Cd in water medium was observed in dry season, and Cu seems to retain in the sediment in both dry and wet seasons. Compared to the unextractable fraction, the extractable was very low, therefore Geloina sp. was used as biomonitor for dissolved Cd and Hg, and Zn in sediment. Generally, the heavy metal concentration in Geloina sp. was higher in dry season than in wet season, but no Cu uptake was detected. Therefore, the establishment of limit values of heavy metals in sediment is highly recommended.